2014
DOI: 10.1073/pnas.1406233111
|View full text |Cite
|
Sign up to set email alerts
|

Sequential combination therapy of ovarian cancer with degradable N -(2-hydroxypropyl)methacrylamide copolymer paclitaxel and gemcitabine conjugates

Abstract: For rapid and effective clinical translation, polymer-based anticancer therapeutics need long circulating conjugates that produce a sustained concentration gradient between the vasculature and solid tumor. To this end, we designed second-generation backbone-degradable diblock N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer carriers and evaluated sequential combination therapy of HPMA copolymer-paclitaxel and HPMA copolymer-gemcitabine conjugates against A2780 human ovarian carcinoma xenografts. First, exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
100
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 34 publications
4
100
0
Order By: Relevance
“…It was demonstrated that the combination of PTX and GEM is schedule-dependent; treatment with PTX followed by GEM has the strongest synergism [60] (Fig. 6.I).…”
Section: The Development Of the Second Generation Of Hpma Copolymementioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the combination of PTX and GEM is schedule-dependent; treatment with PTX followed by GEM has the strongest synergism [60] (Fig. 6.I).…”
Section: The Development Of the Second Generation Of Hpma Copolymementioning
confidence: 99%
“…Combination of gemcitabine with paclitaxel was evaluated on nu/nu mice bearing s.c. A2780 human ovarian carcinoma xenografts [60]. Notably, long retention time of drugs in the circulation is crucial to cell-cycle-specific drugs such as PTX and GEM, which can exert effective actions on cells only in a specific phase of cell cycle.…”
Section: The Development Of the Second Generation Of Hpma Copolymementioning
confidence: 99%
“…poly[N-(2-hydroxypropyl) methacrylamide] (poly-HPMA) has served as a favorable drug delivery carrier owing to its high solubility in water, biocompatibility, and non-immunogenicity [16][17][18][19]. In the early stage in the development of HPMA drug conjugates, HPMA with a high molecular weight (HMW) was directly utilized to conjugate drugs [20].…”
Section: Introductionmentioning
confidence: 99%
“…The sub-units possess a biforked structure with one end conjugated with H1 peptide, and the other end conjugated with a novel fusion targeting peptide (R8NLS) composed of NLS (PKKKRKV) and cell penetrating peptide (octaarginine or R8). The sub-units were conjugated to HPMA polymers via a glycylphenylalanylleucylglycine (GFLG) linker that is lysosomally enzymatic degradable [23,24]. Thus, once the system is internalized into the cell, the sub-units could be unleashed for nuclear transport of the therapeutic peptides.…”
Section: Introductionmentioning
confidence: 99%